Oxidation induced cubic-tetragonal phase transformation in titanium hydride powders. (21st September 2020) - Ben David, R.; Finkelstein, Y.; Grinberg, E.; Samuha, S.; Rabkin, E.; Cohen, D.
Abstract: We studied the effect of oxidation temperature and initial hydrogen concentration on the occurrence of cubic (δ) to tetragonal (ε) phase transformation induced by thermal oxidation of titanium hydride powders in air. X-ray diffraction analysis indicates that δ → ε transformation occurs during oxidation at 400 °C, but not at lower (300 °C) or higher (500 °C) oxidation temperatures. The relative amounts of hydrogen loss during oxidation were determined by temperature-programmed desorption mass spectrometry (TPD-MS). The findings suggest that oxygen stabilizes the tetragonal phase (ε), and that the δ/ε phase composition following oxidation depends on both oxygen and hydrogen concentrations. For high oxidation temperatures (500 °C), some degree of hydride decomposition leads to a decrease in H concentration and to destabilization of the tetragonal phase after cooling down to room temperature. Graphical abstract: Image 1 Highlights: δ → ε phase transformation may occur through powder oxidation treatment in air. Dissolved oxygen stabilizes the tetragonal (ε) phase. The extent of δ → ε conversion strongly depends on the oxidation temperature. Oxygen and hydrogen concentrations affect the δ/ε composition following oxidation. At high temperatures (~500 °C) oxidation is accompanied by partial dehydrogenation.